Physical therapy management of pediatric and adolescent neck pain: a call to action. (3rd September 2019) - Dragotta, Kristen; Jang, Byoungjoon; Quinzi, Brianna; Bosco, Anthony; Clewley, Derek
Abstract: Background : Neck pain is reported to be as high as 40% in adolescents and can be a precursor to developing adult persistent neck pain. Objectives : To identify and review literature on physical therapy management of pediatric and adolescent neck pain. Methods : A sensitive search strategy adhered to PRISMA guidelines. Our systematic review used the databases PubMed, CINAHL, and Embase including articles published from inception to May 2019. For the article to be included, it had to meet the following criteria: (a) age under 18 years old; (b) musculoskeletal neck pain; (c) any intervention or treatment provided by physical therapists; (d) English language; (e) any outcome measure that reported disability, function, or pain; (f) any and all published literature: randomized controlled trials (RCTs), systematic reviews, cohort studies, case reports, editorials, and commentaries. Results : Our comprehensive search yielded 5, 115 articles and two studies met eligibility. Both articles were written by the same author group. The articles investigated the effect of pain neuroscience education (PNE) plus deep neck muscle strengthening in twenty-one students ages 15-18 years old with chronic idiopathic neck pain. The results concluded there may be some benefit to PNE plus deep neck flexor and extensor strength. Conclusions : The main finding of this systematic review is the paucity of published research on physical therapy management of pediatric and adolescent neck pain. Our systematic review serves as a call to action for physical therapists to perform further research in order to provide the best evidence-based care for this population.